Elliptic Equations in Weighted Sobolev Spaces on Unbounded Domains - Serena Boccia; Sara Monsurrò; Maria Transirico (International Journal of Mathematics and Mathematical Sciences)
We study in this paper a class of second-order linear elliptic equations in weighted Sobolev spaces on unbounded domains of ℝ𝑛, 𝑛≥3. We obtain an a priori bound, and a regularity result from which we deduce a uniqueness theorem.